Analysis of 14 Patients With Congenital Nephrotic Syndrome - Chen, Yan; Zhang, Yanqin; Wang, Fang; Zhang, Hongwen; Zhong, Xuhui; Xiao, Huijie; Yao, Yong; Jiang, Yi; Ding, Jie; Hou, Xinlin (Frontiers in Pediatrics, 2019)
From January 1995 to June 2018, 14 patients with congenital nephrotic syndrome (CNS) were diagnosed in the Department of Pediatrics, Peking University First Hospital. The clinical data were retrospectively studied. Eight patients underwent genetic testing; 7 of them had NPHS1 mutations (primary CNS), and 1 did not have a mutation. Of the 7 patients with NPHS1 mutations, 6 died, and 1 had proteinuria. Of the 14 patients, 8 had cytomegalovirus (CMV) infection, and anti-CMV therapy was administered to 7 of them. The other patient was hospitalized in critically ill condition and died before anti-CMV therapy administration. Of the 7 patients who were administered anti-CMV therapy, proteinuria disappeared in 2 patients; 2 patients died; 2 patients were lost to follow up; and 1 patient still had 3+ proteinuria. Three patients had both NPHS1 mutations and CMV infection. After anti-CMV therapy, proteinuria was resolved in 1 patient but relapsed to 3+ proteinuria due to a new infection. The other 2 patients died. Of 14 patients, only 1 patient underwent renal biopsy, with results showing mesangial proliferative glomerulonephritis pathology, negative CMV inclusion body, and CMV-DNA. In this study, genetic defect could play a primary role in CNS, and CMV could play a secondary role. Primary CNS with NPHS1 mutations has a poor prognosis. Primary CNS might be accompanied by CMV infection that responds poorly to antiviral treatment. Secondary CNS caused by CMV infection may be cured with antiviral therapy. However, genetic analysis is necessary to exclude genetic defects.